The KNOWLEDGE AND PREPAREDNESS IN DEALING WITH EARTHQUAKE DISASTER IN NURSING STUDENTS IN SURABAYA AND BANGKALAN - Merina Widyastuti; Nur Muji Astuti; Ninik Ambar Sari Sari; Arju Rohmata; Mufarika -; Agus Haryanto (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Introduction : Knowledge in dealing with disasters is one part of disaster mitigation in the application of disaster preparedness in the campus environment. The death toll from an earthquake will increase along with the knowledge of the community and the level of preparedness they have. This study aims to see the significance of the relationship between knowledge and student preparedness in dealing with earthquake disasters in the campus environment. Method : Research design with descriptive correlational cross sectional approach. Sampling using non-probability sampling technique random sampling The research sample was 237 students at STIKES Hang Tuah Surabaya & STIKES NHM with questionnaires in the period of June- July 2022. Test data analysis using ChiSquare. Results The results showed that the majority of STIKES Hang Tuah Surabaya students had good knowledge of 205 (86.9%) and moderate preparedness of 226 (95.4%). Statistical test results show the value of ρ=0.011 (ρ<α=0.05) which means that knowledge has a close relationship with preparedness in the face of earthquakes. Conclusion The implications of this research can be concluded that increasing knowledge is an important part of mitigation in increasing preparedness in the campus environment in dealing with disaster threats, especially earthquakes in particular.